Hubungan Pola Asuh Orang Tua dengan Perkembangan Sosial Emosional pada Anak Prasekolah - Mayasari, Ade Tyas; Wasirah, Siti; Ati, Purwana Damai; Malinda, Hera; Khotipah, Siti; Soresmi, Soresmi (Utan Kayu Publishing, 2021)
Social-emotional development disorders such as depressive disorders, hyperactivity, and defiant behaviour have an impact on learning achievement, increased risk of mental illness, and physical disorders in adulthood. Factors that can affect the socio-emotional development of preschool children themselves include parenting patterns that include democratic, authoritarian and permissive parenting. The research objective was to determine the correlation between parenting patterns and the social-emotional development in preschool children in early childhood/kindergarten at Tiyuh Kibang Yekti Jaya District, Lambu Kibang District, in Tulang Bawang Barat Regency 2021. The design of this research was an analytical study with a cross-sectional design. The population in this research were parents and pre-school age children in childhood/ kindergarten in Tiyuh Kibang Yekti Jaya Region, Lambu Kibang District, in West Tulang Bawang Regency in 2021, totalling 86 people and all of them were used as samples (total sampling). The analysis in this research used the person chi-square test. The results showed that the parents of preschool children mostly used democratic parenting (53.5%) and the frequency of development of preschool children was mostly in the normal category (37.2%). The results of the analysis of the person chi-square test obtained a p-value of 0.001 (p less than 0.05). The conclusion is that there is a correlation between parenting patterns and the socio-emotional development of preschool children. It is expected that parents can use democratic parenting because this parenting style has advantages in increasing children’s social-emotional development. Abstrak: Gangguan perkembangan sosial emosional seperti gangguan depresi, hiperaktif, dan perilaku yang menentang memiliki dampak terhadap prestasi belajar, peningkatan resiko penyakit mental, serta gangguan fisik di masa dewasa. Faktor yang dapat mempengaruhi perkembangan sosial emosional anak prasekolah sendiri di antaranya pola asuh orangtua yang mencakup pola asuh demokratis, otoriter dan permisif. Tujuan penelitian ini adalah untuk mengetahui hubungan pola asuh orang tua dengan perkembangan sosial emosional anak prasekolah di Paud/TK Wilayah Tiyuh Kibang Yekti Jaya Kecamatan Lambu Kibang Kabupaten Tulang Bawang Barat tahun 2021. Desain penelitian ini adalah studi analitik dengan rancangan cross sectional. Populasi dalam penelitian ini adalah orang tua dan anak usia pra sekolah di PAUD, TK di Paud/TK Wilayah Tiyuh Kibang Yekti Jaya Kecamatan Lambu Kibang Kabupaten Tulang Bawang Barat tahun 2021 yang berjumlah 86 orang dan seluruhnya dijadikan sampel (total sampling). Analisis dalam penelitian ini menggunakan uji person chi square. Hasil penelitian menunjukkan bahwa orangtua anak prasekolah sebagian besar menggunakan pola asuh demokratis (53,5%) dan frekuensi perkembangan anak prasekolah sebagian besar masuk dalam kategori normal (37,2%). Hasil analisis uji person chi square didapatkan p-value 0,001 (p kurang dari 0,05). Kesimpulan terdapat hubungan pola asuh orangtua dengan perkembangan sosial emosional anak prasekolah. Diharapkan orangtua dapat menggunakan pola asuh demokratis karena pola asuh ini memiliki keunggulan dalam meningkatkan perkembangan sosial emosional anak.